2011
DOI: 10.1096/fj.10-174656
|View full text |Cite
|
Sign up to set email alerts
|

Salivary glands act as mucosal inductive sitesviathe formation of ectopic germinal centers after site‐restricted MCMV infection

Abstract: We investigated the hypothesis that salivary gland inoculation stimulates formation of ectopic germinal centers (GCs), transforming the gland into a mucosal inductive site. Intraglandular infection of mice with murine cytomegalovirus (MCMV; control: UV-inactivated MCMV) induces salivary gland ectopic follicles comprising cognate interactions between CD4(+) and B220(+) lymphocytes, IgM(+) and isotype-switched IgG(+) and IgA(+) B cells, antigen presenting cells, and follicular dendritic cells. B cells coexpresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 88 publications
(90 reference statements)
5
41
0
Order By: Relevance
“…In mice, replicating virus at late time points postinfection can be observed in salivary glands, but whether the viral production at this site contributes to the observed antibody inflation remains to be examined. Nevertheless, it has been observed that following intraglandular MCMV infection the salivary gland can operate as a mucosal inductive site for isotype-switched IgG ϩ B cells (46). Moreover, studies by the Reddehase laboratory showed that in other tissues, such as lungs, viral replication is abortive, as only the expression of (immediate) early genes are observed, which nonetheless can lead to stimulating inflationary T cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, replicating virus at late time points postinfection can be observed in salivary glands, but whether the viral production at this site contributes to the observed antibody inflation remains to be examined. Nevertheless, it has been observed that following intraglandular MCMV infection the salivary gland can operate as a mucosal inductive site for isotype-switched IgG ϩ B cells (46). Moreover, studies by the Reddehase laboratory showed that in other tissues, such as lungs, viral replication is abortive, as only the expression of (immediate) early genes are observed, which nonetheless can lead to stimulating inflationary T cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…Do the specific cells or cytokines contribute much to TLS formation and maintenance? And Epstein-Barr virus is thought to be a critical factor that determines TLS formation (91), as is murine cytomegalovirus in the salivary glands (92); therefore, do viruses affect TLS formation/function? In addition, is TLS development driven by different disease subtypes, or are TLS the inevitable result of persistent inflammation?…”
Section: Discussionmentioning
confidence: 99%
“…and Mycobacterium tuberculosis bacteria, as well as influenza and hepatitis C viruses, have been linked with ELF development in mice and humans 77, 78, 79, 80, 81, 82, 83, 84. Interestingly, ELF formation in response to infection features at mucosal sites including lung, gastric and salivary gland tissues 78, 82, 85. ELFs that develop in response to microbiota are also important for maintaining intestinal homeostasis 86.…”
Section: Elfs As Inductive Sites For Anti‐pathogen Immune Responsesmentioning
confidence: 99%
“…T cells expressing CXCR5 displayed Tfh‐ and Th1‐like effector characteristics and were important for host survival, M. tuberculosis clearance, T‐cell localization within ELFs, and lymphoid follicle formation 79. In murine cytomegalovirus infection, lymphoid follicles that form in the salivary glands participate as inductive sites in oral mucosal immunity 85. Development of these salivary follicles was accompanied by a local expression of homeostatic chemokines and molecular markers such as AID and I μ C α (the non‐excised rearranged DNA of IgA class‐switching), which regulate germinal centre activities including somatic hypermutation and class‐switch recombination 85…”
Section: Elfs As Inductive Sites For Anti‐pathogen Immune Responsesmentioning
confidence: 99%